(untitled) (مجلة جامعة اللاذقية- سلسلة العلوم الاقتصادية والقانونية, 2019)
البطالة مشكلة ذات أبعاد اقتصادية واجتماعية، وهي ظاهرة مرضية تتجلى في عدم وجود فرص عمل مشروعة لمن توافرت له القدرة على العمل والرغبة فيه، فهي تعني عدم القدرة على توظيف واستثمار الطاقات البشرية للإنتاج، وإهدارها مما يعرقل حركة التنمية ويعطل حركة الدفع نحو مجتمع منتج. وتتجلى خطورة المشكلة في التزايد المستمر في أعداد العاطلين عن العمل وما تخّلفه هذه السياسة وراءها من نتائج اجتماعية وسياسية ونفسية، باعتبارها البيئة المواتية لنمو مظاهر العنف والجريمة والتطرف. وبالتالي فإن حل هذه المشكلة من شأنه مواجهة التفكك الاجتماعي والأسري، والمساهمة في إعادة توجيه الطاقات البشرية المتاحة، والتقليل من الاضطرابات السياسية والنفسية والاقتصادية، وهذا يعني بالضرورة التأكيد على أهمية تحقيق التنمية، وتحديد خطوات ومقترحات فعلية وضمن الظروف الراهنة المحيطة من أجل وضع حد لتفاقم هذه المشكلة. Unemployment is a problem that has economic and social dimensions. It is a unhealthy phenomenon that manifests itself in the absence of legal job opportunities to those who have the ability and the willingness to work. It means the inability of recruiting and investment the manpower for production, Thereby hampering the movement of development and hindering the movement towards a productive society. The seriousness of this problem is manifested in the ever-growing numbers of unemployed and in the social, political and psychological consequences for this policy as the suitable environment for growing the aspects of violence, crime and extremism. Therefore the solution of this problem would face family and social disintegration, and would contribute to the reorientation of the availability human resources, and reduce the psychological, economic and political turmoil. This means necessarily emphasize the importance of achieving development, and identify steps and concrete proposals, within the current circumstances surrounding to put an end to exacerbate the problem.